Restaurants’ compliance with calorie labeling policies in food delivery applications - Alangari, Abdulaziz S. (Frontiers in Nutrition, 2023)
Background: To encourage consumers to make healthier choices, the Saudi Food and Drug Authority (SFDA) released the Saudi Arabia Nutrition Labeling Policy, which requires restaurants to present caloric information clearly on their menus. Food delivery applications are also mandated to present caloric information on their platforms. The aim of this study is to explore how restaurants on food delivery applications comply with the calorie labeling policy. Methods: Data were extracted from a widely used food delivery application in Saudi Arabia to include a sample of 120 "healthy food" restaurants. The restaurants were checked for compliance on both the application and the website. Descriptive and logistic regression analyses were performed to examine the distribution and association of relevant factors.Results: A substantial proportion (43.3%) of healthy foods on delivery applications (n=120) do not comply with the SFDA calorie labeling policies. Among these restaurants, 56.5% presented the calorie labeling on their menu item. Of those who provided calorie information on their websites (n=62), 54.8% provided appropriate calorie labeling based on the SFDA policy. There was an association between compliance and the number of restaurant categories but no associations for website calorie labeling, rating, and appropriateness.This study provides important findings for policymakers that will enable them to reinforce food calorie policies on food delivery platforms, restaurant websites, social media, and marketing campaigns. Not all restaurants comply with the SFDA calorie labeling policies. Suggestions to present the calorie-related words in Arabic and offer more information to help the consumer make the appropriate food selection decision. Further studies are needed to explore the reasons for and barriers to posting nutritional information on menu items.